43‐3: 14 Inch Flexible LCD Panel with Colorless Polyimide. Issue 1 (29th May 2019) - Shi, Yu; Li, Zhuhui; Wang, Kaijun; Yuan, Chunge; Xie, Huafei; Lu, Macai; Liu, Nian; Huang, Qiao; Zhang, Li; Fan, Jack; Zhao, Xianping; Jing, Xiaohong; et al.
Abstract : We successfully realized 14 inch flexible LCD display with FHD resolution. The LCD panel has the thickness less than 0.3 mm, which using new type of colorless PI as substrate. The flexibel LCD is IPS mode. The key technology includes the conbination of indium gallium zinc oxide (IGZO) TFT, Color filter on Array substrate(COA)and Black Photo Spacer(BPS).